Planning of integrated/sustainable solid waste management (ISWM) - model of integrated solid waste management in Republika Srpska (BiH) - Topić, Milan; Biedermann, Hubert (Serbian Journal of Management, 2015)
Municipal solid waste management (MSWM) has become an important issue for countries around the world. The challenges are particularly notable in developing and transitional countries reflected mainly in inappropriate management, underdeveloped technology, an unfavorable economic situation and the lack of environmental awareness, causing a tremendous environmental impact. Today, various models are applied to analyze solid waste management systems from the regional to the municipal levels. Understanding the mechanisms and factors that currently drive the development of waste management is a crucial step for moving forward and planning sustainable waste management systems. The main objective of this paper is to apply the ISWM model, which is based on the Life-Cycle approach and follows the analytical framework methodology, to the research region. The trans-disciplinary research framework was empirically tested and subsequently applied in the region Republika Srpska. Using the benchmark methodology, based on environmental, institutional and economical sustainability, the waste management is summarized in assessment profile. The results of the conducted analyses and the application of the developed model can be used further as a basis for the proposal of further strategic, political and managerial changes and support decision makers and stakeholders to handle waste in a cost-efficient and environmentally sound way.